Impact of intertumoral heterogeneity on predicting chemotherapy response of BRCA1-deficient mammary tumors - Rottenberg, Sven (2012)
The lack of markers to predict chemotherapy responses in patients poses a major handicap in cancer treatment. We searched for gene expression patterns that correlate with docetaxel or cisplatin response in a mouse model for breast cancer associated with BRCA1 deficiency. Array-based expression profiling did not identify a single marker gene predicting docetaxel response, despite an increase in Abcb1 (P-glycoprotein) expression that was sufficient to explain resistance in several poor responders. Intertumoral heterogeneity explained the inability to identify a predictive gene expression signature for docetaxel. To address this problem, we used a novel algorithm designed to detect differential gene expression in a subgroup of the poor responders which could identify tumors with increased Abcb1 transcript levels. In contrast, standard analytical tools, such as Significance Analysis of Microarrays (SAM), detected a marker only if it correlated with response in a substantial fraction of tumors. For example, low expression of the Xist gene correlated with cisplatin hypersensitivity in most tumors, and it also predicted long recurrence-free survival of HER2-negative, stage-III breast cancer patients treated with intensive platinum-based chemotherapy. Our findings may prove useful for selecting patients with high risk breast cancer who could benefit from platinum-based therapy.